2015
DOI: 10.1063/1.4923245
|View full text |Cite
|
Sign up to set email alerts
|

Low-noise cold-field emission current obtained between two opposed carbon cone nanotips during in situ transmission electron microscope biasing

Abstract: Low-noise cold-field emission current obtained between two opposed carbon cone nanotips during in situ transmission electron microscope biasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Bright field electron holography can be used to map the sample thickness [5], the mean inner potential of a sample [6], the electrostatic field [7] as well as the magnetic field [8] with sub nanometric resolution. More re-Preprint submitted to Elsevier cently, it has been shown that electron holography allows the charge on individual nanoparticles to be measured to a precision of one elementary unit of charge [9] or monitor in-situ the field emission from carbon cone nanotips [10]. In addition, based on the interference of one diffracted beam originating from two areas with different strain states, darkfield electron holography allows mapping the strain field with nanometer scale spatial resolution [4].…”
Section: Off-axis Electron Holography In a Transmissionmentioning
confidence: 99%
“…Bright field electron holography can be used to map the sample thickness [5], the mean inner potential of a sample [6], the electrostatic field [7] as well as the magnetic field [8] with sub nanometric resolution. More re-Preprint submitted to Elsevier cently, it has been shown that electron holography allows the charge on individual nanoparticles to be measured to a precision of one elementary unit of charge [9] or monitor in-situ the field emission from carbon cone nanotips [10]. In addition, based on the interference of one diffracted beam originating from two areas with different strain states, darkfield electron holography allows mapping the strain field with nanometer scale spatial resolution [4].…”
Section: Off-axis Electron Holography In a Transmissionmentioning
confidence: 99%
“…Off-axis electron holography, in combination with in situ electrical measurements, has previously been used to map local variations in electrostatic potential in samples that include electrically biased W microtips, 13 field emitting C nanotubes, 14 C cone nanotips 15 and p−n junctions in semiconductors. 16 In such applications, careful experimental design can be used to determine and subtract the contribution to the measured phase shift from the mean inner potential (MIP) of the specimen in order to retrieve the electrostatic potential associated with additional charge redistribution, such as that resulting from the presence of an applied voltage.…”
mentioning
confidence: 99%